Karier Subkultur dan Kelompok Marginal: Menelaah Potret Profesi Dominatrix dalam Serial Netflix “Bonding” - Prasakti Ramadhana Fahadi (Universitas Gadjah Mada, 2020)
The competition for jobs in big cities tends to be tougher for the members of groups that are marginalized and socially stigmatized. As a consequence, alternative cultures and vocations emerge. An example of this is the role of professional dominatrix in the kink or alternative sexuality subculture. Using interpretive analysis method, this article studies youth with other marginal identities—namely ‘woman’, ‘homosexual’, and ‘working-class member’ — in regards to their choice to pursue their career in kink subculture as a professional dominatrix in Netflix’s show Bonding. The findings of this research are as follows: The legitimation of alternative sexuality industry as a metropolitan subculture; young people choose to pursue a career, especially in subcultural industry, as a platform as well as motivation for self-actualization, and; jobs in sex and alternative sexuality industry are taken by marginalized young people as an effort to make a living in a big city.